(untitled) - Josephson, Paul R. (New York, 1996)
Contents: Totalitarian science; Transformationist visions; The physical sciences under totalitarian regimes; Technology and politics in totalitarian regimes.
Keywords: Khoa học,Science; Khía cạnh xã hội,Lịch sử,Social aspects,History